OLFACTORY NEUROBLASTOMA PRESENTING AS BLEEDING POLYP - Niazi, Saleem Asif; Saeedullah, Saeedullah (Journal of Ayub Medical College Abbottabad, 2012)
Malignant tumours of the nasal cavity are rare. Olfactory neuroblastomas (esthesioneuroblastomas) account for only 6% of these neoplasms. Fewer than 1,000 cases have been reported in the literature since this tumour was first described more than 75 years ago. A 13 year old girl presented with bleeding nasal polyp to ENT Department. She was operated as there were no signs of tumour the histopathology report revealed it to be olfactory neuroblastoma. As there was no intracranial extension she was given postoperative radiotherapy. Keywords: olfactory neuroblastoma, bleeding polyp, nasal, epistaxis